PENENTUAN PRIORITAS PERBAIKAN KUALITAS LAYANAN KESEHATAN DENGAN METODE SERVQUAL - Hana Catur Wahyuni; Wiwik Sulistiyowati (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2015)
Abstract The quality of health services is required by the health implementing-organization as a strategy to win the competition. In order to improve the quality of health services, there should be a sustainable improvement in all aspects of quality. This study aims to perform the identification of the quality of the existing services and determine the priorities for resolving the problem and improving the customer satisfaction. It applies Servqual method with five dimensions: tangible, responsiveness, reliable, assurance and empathy; and 25 research attributes. The questionnaires given to the respondents consist of three things: a questionnaire for the identification of the respondents, of the level of customer perception and of the level of customer expectation. The research results that the highest gap between the consumer perception and the consumer expectation found in the dimension of empathy and the attributes of the medical workers’ patience and amiability during health examination with the value of -1.05. These results indicate that the priority of health care quality improvement is by increasing the medical workers’ ability in doing health examinations with patience and amiability.